STRATEGI PENINGKATAN MUTU PERTANIAN PERKOTAAN UNTUK KETAHANAN PANGAN DI PROVINSI BALI - Putu Adi Wiratenaya; Ni Nyoman Yuliarmi (Jurnal Penjaminan Mutu, 2022)
Food is a basic human need therefore food security has always been an interesting topic. However, realizing food security is often faced with many challenges. The agricultural sector and the tourism sector are very important for the Balinese economy, but since the Covid-19 pandemic the tourism sector has decreased. As a result of the decline in the tourism sector, many workers in the tourism sector have turned to the agricultural sector by cultivating fields or just using their yards. More and more people are interested in trying urban farming. However, there are many obstacles faced by urban farming, such as the absence of regulations on urban farming, and the absence of an institution that protect urban farming communities in the Bali region, and effective marketing methods. This research was conducted by literature study method. Agriculture is a very risky sector, so government support is needed